Adaptation and validation of the memorial anxiety scale for prostate cancer (MAX-PC) in a sample of French men - Rajae Touzani; Julien Mancini; Jaïs Troïan; Anne-Déborah Bouhnik; Olivier Cussenot; Gwenaelle Gravis; Patricia Marino (SpringerOpen, 2019)
Abstract Introduction The Memorial Anxiety Scale for Prostate Cancer (MAX-PC, 18 items) was developed to assess anxiety in prostate cancer patients. In the absence of a French version of this scale, we adapted the original English scale and evaluated its psychometric properties in a sample of French men diagnosed with prostate cancer in the previous 12 months. Methods The MAX-PC was translated from English to French and distributed online by two non-profit organizations (Seintinelles and ANAMACaP). The French questionnaire, which also included the Hospital Anxiety and Depression Scale (HADS) and a measure of health-related quality of life (SF12), was intended for adults diagnosed with prostate cancer in the previous 12 months. Factor structure was assessed using exploratory factor analysis (EFA) on data from 56.2% of the sample (n = 104, Seintinelles subsample) and confirmed using confirmatory factor analysis (CFA) on data from the rest of the sample (n = 81, ANAMACaP subsample). The reliability of the scale was measured using Cronbach's alpha coefficient. Construct validity was assessed by calculating the correlation of the MAX-PC total score and subscale scores with the HADS total score and subscale scores and with the SF12 total score and subscale scores. Results Of the 185 respondents, 168 (90.8%) had complete data on all MAX-PC items. The average age of participants was 65.1 years (SD: 7.7). The three-factor structure defined in the original validation study was very similar in EFA and then confirmed by CFA. The MAX-PC showed good reliability, as Cronbach's alpha coefficients for the scale and for its three subscales were 0.92, 0.90, 0.68, and 0.87, respectively. It also showed good construct validity. As expected, the MAX-PC total score was positively correlated with the HADS-Anxiety subscale score (r = 0.68, p < 0.001) and negatively correlated with the SF12-MCS subscale score (r = − 0.35, p < 0.001). Conclusion The French version of the MAX-PC shows adequate psychometric properties among French men with prostate cancer. This scale may be used in future studies and in routine clinical care to help health care providers identify patients who need psychological support due to prostate-cancer related anxiety.